Desarrollo de plataforma UAS de ala ja para aplicaciones de Fotogrametría - Gutierrez-Leiva, Edgar Mario (Instituto Tecnológico de Costa Rica, 2017)
The conventional methods for estimating soil erosion, compromise result's reliability due to the complex installation of measuring instruments. Particularly Costa Rica is a ected by this phenomenon. The Electronics Engineering School of the Instituto Tecnol ogico de Costa Rica, has been researching alternatives for soil erosion quanti cation. One of these is by using unmanned aerial systems (UAS) through the aerial photogrammetry technique, showing great results and presenting a greater precision without altering the study area. In the case of large-scale photogrammetry applications, the use of multi-rotor platforms presents a high consumption of resources and time. The xed-wing systems due to their low energy consumption and their ability to reach higher speeds, represents a great alternative compared with multi-rotor systems. The present work shows the process of design and development of a xed-wing type UAS platform for photogrammetry applications. This system must be able to carry out ight missions autonomously and collect the necessary information for soil analysis.
Proyecto de Graduación (Licenciatura en Ingeniería Electrónica) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Electrónica, 2017.
Keywords: Fotogrametría; Sistemas; UAS; Research Subject Categories::TECHNOLOGY::Electrical engineering, electronics and photonics::Electronics